2017
DOI: 10.1097/cmr.0000000000000386
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent radiotherapy for patients with metastatic melanoma and receiving anti-programmed-death 1 therapy: a safe and effective combination

Abstract: A combination of immune-checkpoint inhibitors and radiation therapy (RT) represents a promising therapeutic strategy in part mediated by the abscopal effect, but clinical experience related to this combination remains scarce. Clinical data and patterns of treatment were retrospectively collected from all consecutive patients with metastatic melanoma and receiving programmed-death 1 (PD-1) immune-checkpoint inhibitors. Survival data, best overall response, and acute and delayed toxicities (graded according to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 23 publications
5
64
0
1
Order By: Relevance
“…Outcomes of some retrospective studies using that combination with intra-or extracranial palliative irradiation, mostly to treat melanomas, indicated no excessive anti-PD-1 or radiotherapy toxicity. 13,15,16 Clinical trials testing the combination of irradiation and PD-1/PD-L1 inhibition have been initiated, but the results are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of some retrospective studies using that combination with intra-or extracranial palliative irradiation, mostly to treat melanomas, indicated no excessive anti-PD-1 or radiotherapy toxicity. 13,15,16 Clinical trials testing the combination of irradiation and PD-1/PD-L1 inhibition have been initiated, but the results are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of immunotherapy (anti‐programmed death 1 [PD‐1] monoclonal antibody and/or anti‐cytotoxic T‐lymphocyte‐associated antigen 4 [CTLA‐4] monoclonal antibody) on mucosal melanoma is lower in comparison with cutaneous melanoma, as there are critical genetic differences that have not yet been fully explored, and mucosal melanoma rarely has BRAF mutations . Thus, the combination of radiotherapy (RT) and concomitant anti‐PD‐1 antibody therapy is often applied as the first‐line treatment for mucosal melanoma of the nasal cavity in our institute because preclinical data have shown that combinations of immune checkpoint inhibitors (ICI) and RT improved the response of these patients …”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy can liberate and activate CD8+ T cells from an immunosuppressed state, thereby increasing the probability of abscopal effects . Reports of abscopal effects have increased along with the development of combined radiotherapy and immunotherapy, but these have mainly occurred in patients with highly immunogenic melanomas …”
Section: Discussionmentioning
confidence: 99%